The First Word Recalled Measure – A Potential Addition to Clinical Exams - Shapira-Lichter, Irit; Oren, Noga; Asvadurian, Anita; Ben-Hayun, Rachel; Fisher, Tali; Aharon-Peretz, Judith; Glik, Amir (Frontiers in Neurology, 2021)
Characterizing episodic memory abilities is highly important in the diagnosis of Alzheimer’s disease (AD) and mild cognitive impairment (MCI), and usually includes wordlist learning and recall tasks. Clinical evaluations typically focus on the number of words recalled, ignoring additional information, like serial position. Here, we tested the potential value of two serial positioning measures for clinical diagnosis – how retrieval is initiated, as measured by the first word recalled, and how it proceeds – using data from patients with AD and MCI that completed a wordlist learning and recall task. Our results show that during the early stages of learning, patients with AD are less prone to retrieve the first word from the wordlist, manifested as lower primacy effect in the first word recalled, compared with MCI patients. The first word recalled measure adds to the differentiation between the groups over and above the total number of words learned. Thus, the first word recalled during word list learning and recall tasks may be used as a simple complementary measure to distinguish between MCI and AD during standard neuropsychological evaluations.